Penerapan Problem Based Learning Berbantuan Aplikasi Patik Bali untuk Meningkatkan Hasil Belajar Materi Pasang Aksara Bali - Dwi Rahayu, Luh Bulaning (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Most of the students' basic ability to write Balinese characters needs to be improved. This can be seen when students are given discourse in Balinese characters, most of them complain and say that they cannot read. Some students are indifferent because they really cannot read Balinese characters. The lack of basic ability to write Balinese script makes students less interested in Balinese script material. From the assessment of learning outcomes, it also looks very low, where out of 30 students only 1 participant gets a score above the KKM. Therefore, action research must be conducted with the title Penerapan Model Pembelajaran Problem Based Learning Berbantuan Media Aplikasi Patik Bali untuk Meningkatkan Hasil Belajar Materi Pasang Aksara Bali pada Peserta Didik Kelas VII4 SMP Negeri 5 Kuta Selatan Semester Ganjil Tahun Pelajaran 2023/2024. This research was conducted using a type of Classroom Action Research (PTK) consisting of pre-cycle, cycle I, and cycle II. From the research conducted, student learning outcomes have increased from pre-cycle to cycle II. This can be seen in the pre-cycle, out of 25 students who were complete as many as 6 students (24%) and those who were not complete were 19 students (76%). Whereas in cycle I, there were 15 students (60%) who were complete and 10 students (40%) who were not complete. Then in cycle II the students who were complete were 25 students (100%). So from pre-cycle to cycle I there was an increase in learning outcomes by 16%, while from cycle I to cycle II there was an increase in learning outcomes by 40%. With the acquisition of these data, it can be concluded that the application of a problem-based learning model with the Balinese patik application media can improve the learning outcomes of pairs of Balinese characters for students in class VII4 SMP Negeri 5 Kuta Selatan in the 2023-2024 academic year.